PELAKSANAAN PEMBELAJARAN FIQIH DI MADRASAH IBTIDAIYAH AN NAJAH DESA HAUR KUNING KECAMATAN BERUNTUNG BARU KABUPATEN BANJAR - Muhammad Irhamni; Saifuddin Saifuddin (Program Studi PGMI STAI Al Falah Banjarbaru, 2018)
This study discusses the implementation of fiqh learning in the Ibtidaiyah Madrasah An Najah Village Haur Kuning, Beruntung Baru District, Banjar District and the factors that influence it. The subject of this research is one teacher of fiqh subjects and students in Ibtidaiyah Madrasah AnNajah, Haur Kuning Village, Beruntung Baru Subdistrict, Banjar Regency, and the object of this research is the implementation of fiqh learning in Madrasah Ibtidaiyah An Najah Desa Haur Kuning, Beruntung Baru District, Banjar Regency. To obtain data, researchers used observation, interview, and documentation techniques. Data processing techniques are carried out by editing, data classification, and data interpretation. Then analyzed with qualitative descriptive analysis and deductively drawn conclusions. From the results of this study obtained an overview of the implementation of jurisprudence learning in Madrasah Ibtidaiyah An Najah Haur Kuning Village, Beruntung Baru District, Banjar Regency, namely fiqh learning planning has been carried out well because teachers make annual programs, semesters, syllabus and learning implementation plans (RPP). Fiqh learning is carried out well, because at the time of delivery of the subject matter with the right and varied methods and the use of the media even with very limited media. The evaluation was carried out well, the teacher carried out pre-tests, post-tests, and assessment of processes and results. Factors that influence the learning of jurisprudence such as the background are in accordance with the field he teaches and the teaching experience is long enough. Student interest is quite good because students are quite active in the learning process. The environment outside of school strongly supports the process of learning jurisprudence. While the facilities and infrastructure factors are quite complete but rarely used. Keywords: Learning, Fiqh, Madrasah Ibtidaiyah.